Small Businesses in South Africa : Who Outsources Tax Compliance Work and Why? - Coolidge, Jacqueline (2012)
The authors use firm-level survey data on 998 small and medium enterprises registered for tax in South Africa regarding tax compliance costs to investigate the use of outsourcing to complete tax compliance tasks. Overall, about 43 percent of the enterprises do all their tax compliance work in-house, 11 percent outsource all their tax compliance work, and the remaining 46 percent use a combination of both ("partial outsourcing"). The data display an inverted-U shape for outsourcing of tax compliance tasks: the smallest firms (those under R 300,000 turnover or well under US$50,000) tend not to outsource, due to a combination of relatively higher cost-burden and less complexity. Relatively larger firms (those with more than R 14 million turnover or about US$2 million) report that they have sufficient in-house capacity and therefore do not need to outsource. Those in the middle are most likely to outsource at least some of their tax compliance work, mostly because tax is a specialist field and they presumably lack sufficient capacity in-house. The survey data show that the costs of tax compliance are clearly the highest for those who engage in partial outsourcing, as it appears there is likely duplication of effort. Most such firms could reduce their tax compliance costs (and probably minimize the incidence of post-filing problems) by moving from partial to full outsourcing of all tax compliance work.